Peran Penghangat Aktif dan Pasif terhadap Pencegahan Hipotermia Intraoperatif pada Pasien Pediatrik: Literature Review - Radina Dinova Ramadanis; Nasywa Natania Savira; Jihan Artika Prastiwi; Bening Zahwa Islamaya; Ratih Kusuma Dewi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Hypothermia during surgery is a common occurrence among pediatric patients due to their immature thermoregulation system, higher body surface area-to-weight ratio, and thinner subcutaneous fat layer. This condition can lead to several complications, including increased bleeding, coagulation disorders, surgical wound infections, and delayed healing. Prevention strategies include active and passive warming methods. The purpose of this study is to evaluate the effectiveness of active and passive warming in preventing intraoperative hypothermia in pediatric patients. A scoping review approach was applied to interpret the evidence based on predetermined inclusion and exclusion criteria, followed by data exploration, analysis, and synthesis of findings. The results indicate that active warming methods—such as forced-air warming, blanket warming, and warmed intravenous fluids—are more effective than passive warming in maintaining normothermia during surgery. Moreover, combining both approaches provides optimal prevention against hypothermia. Overall, active warming plays a vital role in stabilizing body temperature and enhancing patient safety during pediatric surgery. Therefore, its implementation should be considered a standard practice in perioperative nursing care.